Flight Profile Analysis: Finding Correlations using Scatter Plot Method and Evaluation of Scatter Plot - Mohd Harridon; Mohd Rizal (Institut Teknologi Bandung, 2019)
This paper analyzed flight profiles where parameters of the trajectory of the airplane were found to be correlated in some way. The Scatter Plot Method was used to find these correlations but somehow the degree of correlations was mixed. We proceeded by evaluating the usage of Scatter Plot where Scatter Plot seems to have a good prospect